Efektivitas Kampanye Promosi Kesehatan Dalam Meningkatkan Pengetahuan Dan Perilaku Sehat Masyarakat - K, Hairuddin; Mayasari, Eka; Serli, Serli; Werdyaningsih, Endang; Yulis, Dian Meiliani (Barongko: Jurnal Ilmu Kesehatan, 2025)
Health promotion campaigns are an important strategy for increasing public awareness, knowledge, and behavioral change toward a healthy lifestyle. This study aims to evaluate the effectiveness of health promotion campaigns in increasing knowledge and changing healthy behaviors among the public. A quantitative method was used with a pretest-posttest design without a control group. A total of 150 respondents from three sub-districts were selected purposively. The results showed a significant increase in health knowledge (p<0.05) and behavioral changes such as handwashing, regular exercise, and nutritious food consumption. These findings indicate that health promotion campaigns are effective as a public education tool. It is recommended that campaigns be conducted sustainably and involve various media and local cultural approaches.